Meningkatkan Pengetahuan Pasangan Usia Subur dan Lansia tentang Hipertensi - Imas Nurjanah; Efril Serliana Maulida; Fadia Rasyidin (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The World Health Organization (WHO) reports that cardiovascular disease and hypertension rank as the second most prevalent health conditions among the elderly, following arthritis. These conditions affect 15.2% of a surveyed population of 1,203 individuals. In response to this, the present study seeks to enhance the knowledge of Fertile Age Couples (PUS) and older adults about hypertension prevention and management. The method employed involves in-person counseling supported by educational tools such as booklets and leaflets. The effectiveness of the intervention was assessed through pre-tests and post-tests, each comprising 10 questions. Findings revealed that, prior to counseling, 11 out of 30 participants (36.7%), selected through total sampling, demonstrated good knowledge. Following the intervention, this figure rose to 26 individuals (86.7%), reflecting an 18.28% increase. Moreover, the p-value recorded was <0.000, signifying a statistically significant impact of the educational intervention on improving hypertension awareness among PUS and the elderly. Overall, the study confirms the success of the intervention in raising awareness and understanding of hypertension, which may help lower its occurrence within the targeted population.